Master of the air : William Tunner and the success of military airlift - Slayton, Robert A. (UPCC book collections on Project MUSE., 2010)
In 1948, just as the Cold War was settling into the form it would maintain for nearly half a century, major antagonists the US and the USSR began maneuvering into a series of dangerously hostile encounters. Trouble had broken out in Poland and Czechoslovakia, but it was in Germany, which had been at the heart of World Wars One and Two, that the first potentially explosive confrontation developed. The USSR, which had suffered more at Germany's hands than the rest of the Allies combined, may have viewed developments there with heightened fear and irritability. When the western Allies moved to co.